(untitled) (Marketing Journal, 2026)
Abstract This article provides a scientific analysis of effective strategic directions for increasing the inflow of foreign direct investment (FDI) into the economy of Uzbekistan. Based on the transformation of global investment flows, processes of technological modernization, and the national economic development strategy, the institutional, sectoral, and regional mechanisms for attracting FDI are examined. An integrated strategic model is proposed on the basis of statistical data and current investment programs. Keywords: foreign direct investment, investment climate, industrial transformation, global value chain, export diversification, free economic zones, ESG, technology transfer.